The Impact of Vegetarian and Vegan Nutrition on Health from a holistic point of view and its repercussions on the Intestinal Microbiota (Research, Society and Development, 2022)
The human intestinal microbiota, which can be characterized as a complex and dynamic ecosystem permeated by a harmonic and mutualistic symbiosis, is congregated by varying rates of bacteria, viruses, protozoa and fungi, harboring approximately one hundred trillion microorganisms. In addition, there is a close correlation between intestinal dysbiosis and numerous non-communicable diseases, in addition to interactions between the gut microbiota and the brain, termed as constituents of the “gut-brain axis”, which play a key role in neurological dysfunctions. Vegetarianism and Veganism are considered dietary patterns based on the intake of plant-based foods and the total or partial exclusion of specific food groups of animal origin, with a significant and dynamic variation in the stratification of this food activism. In view of the above, the present study seeks to gather evidence regarding the impact of vegetarian and vegan nutrition on health from a holistic and integrated point of view, also considering its repercussions on the intestinal microbiota and the pursuit of pathological processes. Therefore, a study was carried out through a narrative literature review, through consultations in the following databases: SciELO, PubMed MDPI, Google Scholar, Karger Publishers and BioMed Central. In addition, twenty-four references consistent with the last fourteen years were used, that is, between 2009 and 2022. In summary, it was raised that vegetarian and vegan diets, when properly designed, are configured as nutritionally balanced. and can cooperate in the prevention and treatment of designated pathologies.